Neighborhood scale traffic pollutant dispersion subject to different wind-buoyancy ratios: A LES case study in Singapore - Mei, Shuo-Jun; Zhao, Yongling; Talwar, Tanya; Carmeliet, Jan; Yuan, Chao (Building and environment, 2023)
This study explores the buoyancy effect on traffic pollutant dispersion at neighborhood scale, in which a wide range of wind-buoyancy ratios is examined. Pollutant dispersion is solved using a Large Eddy Simulation (LES) turbulence model, where realistic urban morphology and historical traffic pollutant emission data are adopted. For no incoming wind condition, thermal plumes develop and entrain horizontal flow near ground level. This neighborhood scale buoyancy-driven flow leads to air pollutant dispersion, which is as strong as wind-driven dispersion in the target area. As a result, urban air pollutant accumulation is limited due to buoyancy, regardless of ambient wind conditions. A light incoming wind can flush upward thermal plumes downstream when the Richardson number (Ri) reaches 25.5. The interplay of the approaching wind and upward plumes from urban surfaces leads to an oscillatory flow, which intensifies local turbulence and enhances the pollutant removal rate. At the pedestrian level, the neighborhood scale average NO2 concentration due to the traffic emission ranges from 4.1μg/m3 to 4.8μg/m3. The minimum value is found for a weak incoming wind condition, (coupling with buoyancy, Ri = 25.5) and the maximum value is observed for the no incoming wind condition (Ri = ∞). The modelling result analysis clarifies how buoyancy-related dispersion, emission location, surrounding urban density, and incoming wind affect local pollutant concentrations. The research outputs highlight the importance of these coupling effects in the air pollutant dispersion evaluation in real urban areas. •Large variations in wind-buoyancy ratio (Ri=1.0∼∞) are considered.•Neighborhood scale buoyancy is strong enough to drive traffic pollutants removal.•Maximum urban air pollutant concentration is limited due to thermal buoyancy.•Minimum pollutant concentration is observed in light wind and strong buoyancy.•Pollutants at pedestrian level show little dependence on wind when heat condition is severe.